Peningkatan Kemampuan Menulis Cerita Pendek dengan Menerapkan Model Pembelajaran Brainwriting pada Siswa Kelas XI SMA IT Granada Samarinda - Elvina Damayanti; Meita Setyawati; Kukuh Elyana (Institut Nalanda, 2025)
Writing is expressing thoughts, feelings, experiences, and the results of reading in written form, not in spoken form. Being proficient in a language means being skilled in writing; writing skills are essentially not just the ability to write graphic symbols that form words, and words can be arranged into sentences according to certain rules, but writing skills are the ability to pour thoughts into written language through sentences that are arranged completely, fully, and clearly. Thus, the results of that thought can be effectively communicated to the reader. Writing skills do not appear automatically and suddenly, but must go through practice and repeated and regular exercises. In practice, students need motivation and encouragement from teachers when learning writing in the classroom. This research aims to enhance the short story writing learning process by applying the brainwriting learning model to XI grade students at IT Granada High School in Samarinda with a total of 25 students. This type of research is a classroom action research. The research was conducted in two cycles, with stages of research including planning, implementation, observation, and reflection. Writing short stories can be a choice for students to practice expressing their experiences, thoughts, feelings, and beliefs. This will train students to express what is within them so that it can be accepted or recognized by others. It is necessary to optimize every supporting element, namely the curriculum, teaching materials, learning media, learning strategies, teachers, and students so that learning proceeds as it should. Meanwhile, in line with the learning model used, which is the Brainwriting model, it is a model whose delivery method is through writing or written form. Brain means brain, write means to write, so Brainwriting is writing everything that comes to mind. Brainwriting is a learning model that focuses on expressing ideas about a topic in writing.